Patient's Satisfaction with Health Care Services in Erbil City/Iraq - Dlzar Omer Qadir; Saleem Saaed Qader; Dara Abdulla Al-Banna; Ahmed Ali Rasool; Jamal Kareem Shakor (Hawler Medical University, 2021)
Background and objective: Patient satisfaction is one of the most important factors to determine the success of a health care facility. It is a relative phenomenon, which evaluates the patients' perceived needs, their expectations from a health system, and the experience of health care. Patient satisfaction is the main goal today for most health care organizations, from hospitals to physician practices and other health care agencies. This study aimed to compare patient satisfaction with the health care services provided by public and private hospitals in Erbil City. Methods: A cross-sectional study was conducted using a non-probability purposive sample of 450 patients (225 from public and 225 from private hospitals) who were seeking health care in hospitals in Erbil City. The data were collected between the 7th of January and 15th of November 2016 by direct interviews and filling of the standardized questionnaires (Patient Satisfaction Questionnaire-18). Results and Discussion: Most of the patients in public hospitals expressed a neutral level of satisfaction with received health services (80.9%) while 10.7% were dissatisfied and only 8.4% were satisfied with the provided health care. On the contrary, most of the patients in private hospitals (80%) were satisfied with their care, with only 20% expressing a neutral level of satisfaction with private health care services. These findings show that there is a very high statistical difference between patient satisfaction in the governmental and private hospitals in Erbil City (Mean ± Standard Deviation 45.35 ± 3.520), (56.42 ± 5.696) (p-value= <0.001). Conclusion: Most of the patients were satisfied with private health care services but not with public hospitals health services in selected hospitals in Erbil City in Iraq.